Beyond Survival: Assessing Quality of Life, Activity Level, and Ethnic Diversity in Aortic Dissection Survivors - Nora Bacour; Olivia van Erp; Simran Grewal; Aytug U. Tirpan; Susanne Eberl; Kak Khee Yeung; Ron Balm; Germaine C. Verwoert; Antoine H. G. Driessen; Robert J. M. Klautz; Nimrat Grewal (Journal of Cardiovascular Development and Disease)
Background: An acute aortic dissection (AAD) is a highly lethal condition that demands immediate medical intervention. Survivors often face significant long-term challenges. While immediate survival remains a critical focus in acute care settings, little is known about long-term results, especially with regard to activity levels, post-operative quality of life, and the impact of cultural and ethnic characteristics on recovery. Using data from the Dutch National Aortic Dissection Survivor’s Day, this study examines QoL, activity levels, and ethnic diversity among survivors. Methods: All patients (n = 45) participating in a national awareness meeting for AAD survivors at a teaching hospital were included in our study. Participants completed questionnaires assessing QoL, activity levels, and sociodemographic data, including ethnic background. The EQ-5D and IPAQ surveys were employed to measure health-related QoL and physical activity, respectively. Results: The mean age of the participants was 59.5 years, with 37.8% identifying as women. Ethnically, 88.9% identified as Dutch. The majority reported good health (mean score of 73/100). However, there was a considerable variation in QoL scores. On average, 22.2% of our study population reported moderate or greater problems across all dimensions, compared to 5.5% in the normative sample. Activity levels were mostly low to moderate, and no significant differences in QoL were found based on activity levels. Sleep quality was generally good. Conclusions: Our study reveals significant limitations in QoL among AAD survivors. This emphasizes the significance of developing a multimodal rehabilitation program focused on addressing current gaps in recovery. Ultimately, this will enhance overall care following AAD. Future research should focus on assessing long-term QoL.